2020
DOI: 10.3389/fpubh.2020.572561
|View full text |Cite
|
Sign up to set email alerts
|

Protective Behavior in Course of the COVID-19 Outbreak—Survey Results From Germany

Abstract: Objective: The COVID-19 outbreak means far-reaching changes in the organization of daily lives. Disease-related literacy and factors such as age, gender, or education play a major role in shaping individual practices of protective behavior. This paper investigates different types and frequency of practicing protective behaviors, as well as socio-demographic factors that are associated with such behavioral change. Methods: Data stem from a cross-sectional survey in Germany. Three thousand seven hundred and sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
77
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 30 publications
(32 reference statements)
16
77
0
3
Order By: Relevance
“…Women have been found, in all countries, more likely to perceive COVID-19 as a serious problem, agree with NPIs, and comply with them [24]. Similar results have been found in other studies conducted in Slovenia, Japan and Germany [25][26][27][28]. Age is also an important variable affecting adoption.…”
Section: Introductionsupporting
confidence: 82%
“…Women have been found, in all countries, more likely to perceive COVID-19 as a serious problem, agree with NPIs, and comply with them [24]. Similar results have been found in other studies conducted in Slovenia, Japan and Germany [25][26][27][28]. Age is also an important variable affecting adoption.…”
Section: Introductionsupporting
confidence: 82%
“…In fact, female respondents are found more likely to perceive COVID-19 as a risk, agree and comply with NPIs [195] , [197] , [200] , [212] , [218] . Similar trends are observed for individuals with high level of education [200] , [215] . Age again does not appear to be a monotonic function: very young and old individuals share similar trends.…”
Section: Surveysmentioning
confidence: 93%
“…In fact, young adults have reported a smaller decrease in mobility and old individuals less compliance to NPIs (especially if male) [212] , [218] . It is important to mention that age was not a relevant factor in a survey conducted in Germany [200] . The research points also to a big urban-rural divide and thus to the importance of socio-economic factors when it comes to compliance.…”
Section: Surveysmentioning
confidence: 98%
“…Following a previous study that examined COVIDiSTRESS Global Survey dataset ( Lieberoth et al, 2021 ), three demographics variables, participant' age, gender, and educational level, were employed as covariates. These variables were also employed in the previous studies examining compliance and beliefs on preventive measures ( Alper et al, 2020 ; Daoust, 2020 ; Lüdecke & von dem Knesebeck, 2020 ). The studies reported that the aforementioned demographical factors were significantly associated with behavioral and psychological responses to preventive measures, such as protective behavior, distancing, and COVID-19 conspiracy theories.…”
Section: Methodsmentioning
confidence: 99%